PENGARUH KARAKTERISTIK KOMITE AUDIT TERHADAP KECURANGAN PELAPORAN KEUANGAN (Studi Empiris Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode 2015-2017) - Khairani Erlien Nurliasari; Tarmizi Achmad (Diponegoro Journal of Accounting, 2020)
The purpose of this study is to examine the relationships between audit committee characteristics (independent audit committee, audit committee's financial expertise, audit committee meetings frequency and tenure of the audit committee) on the likelihood of fraudulent financial reporting.           This study uses secondary data from annual reports of manufacturing companies listed on the Indonesia Stock Exchange in 2015-2017. The research sample was taken using a purposive sampling, and categorized into two group based on the calculation of the Beneish M score model namely 101 non-fraud companies and 130 fraud companies. Data analysis includes descriptive statistic, multicollinearity and logistic regression.            The results of this study indicate that the audit committee financial expertise, audit committee meetings frequency and the tenure of audit committee have a significant negative effect on fraudulent financial reporting while the independent audit committee has a non-significant negative relationship on fraudulent financial reporting.